DENDROCHRONOLOGY AS A TOPIC IN TECHNOLOGICAL EDUCATION AT PRIMARY SCHOOLS - TVARŮŽKA, Václav (Trends in education, 2016)
Dendrochronology is a branch that came into existence as a secondary effect of astronomical observation mainly a sunny activity and climatic changes. The paper deals with the description of important connections and presentation of this topic as an innovative topic for education at primary schools. Work with the Pressler auger, measuring of wood grow is very used method for determination of the wood age and artefacts. This topic integrates a huge scale of science disciplines, activities, physical and natural knowledge. This topic is possible to use as a suitable task for practical laboratory work in technological education.
Keywords: Dendrochonology; labolatorní práce; Pressler Dendrochronological borer; výuka; technologie.